ASGE guideline on the role of endoscopy in the management of malignant hilar obstruction - Qumseya, Bashar J.; Jamil, Laith H.; Elmunzer, Badih Joseph; Riaz, Ahsun; Ceppa, Eugene P.; Thosani, Nirav C.; Buxbaum, James L.; Storm, Andrew C.; Sawhney, Mandeep S.; Pawa, Swati; Naveed, Mariam; Lee, Jeffrey K.; et al. (Gastrointestinal endoscopy, 2021)
This clinical guideline from the American Society for Gastrointestinal Endoscopy (ASGE) provides an evidence-based approach for the management of patients with malignant hilar obstruction (MHO). This document was developed using the Grading of Recommendations Assessment, Development and Evaluation framework and addresses primary drainage modality (percutaneous transhepatic biliary drainage [PTBD] vs endoscopic biliary drainage [EBD]), drainage strategy (unilateral vs bilateral), and stent selection (plastic stent [PS] vs self-expandable metal stent [SEMS]). Regarding drainage modality, in patients with MHO undergoing drainage before potential resection or transplantation, the panel suggests against routine use of PTBD as first-line therapy compared with EBD. In patients with unresectable MHO undergoing palliative drainage, the panel suggests PTBD or EBD. The final decision should be based on patient preferences, disease characteristics, and local expertise. Regarding drainage strategy, in patients with unresectable MHO undergoing palliative stent placement, the panel suggests placement of bilateral stents compared with a unilateral stent in the absence of liver atrophy. Finally, regarding type of stent, in patients with unresectable MHO undergoing palliative stent placement, the panel suggests placing SEMSs or PSs. However, in patients who have a short life expectancy and who place high value on avoiding repeated interventions, the panel suggests using SEMSs compared with PSs. If optimal drainage strategy has not been established, the panel suggests placing PSs. This document clearly outlines the process, analyses, and decision processes used to reach the final recommendations and represents the official ASGE recommendations on the above topics. [Display omitted]